Pengurangan Pemakaian Pupuk Anorganik dengan Penambahan Bokashi Serasah Tanaman pada Budidaya Tanaman Tomat - Darwin Habinsaran Pangaribuan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
The aim of the research was to investigate the application of plant compost on the growth and yield of tomatoes. The experiment was conducted in Bandar Lampung from October 2009 until February 2010. The experimental design was completely randomized block design with 3 replications. The treatments were: control; recommended inorganic fertilizers 135 kg N ha-1, 75 kg P2O5 ha-1, and 110 kg K2O ha-1; white leadtree (Leucaena glauca) compost + recommended inorganic fertilizer; legume compost + 50% recommended inorganic fertilizer; teak (Tectona grandis) compost + recommended inorganic fertilizer; teak compost + 50% recommended inorganic fertilizer; paddy straw (Oryza sativa) compost + recommended inorganic fertilizer; paddy straw compost + 50% recommended inorganic fertilizer; rattlepod (Crotalaria anagyroides) compost + recommended inorganic fertilizer; rattlepod compost + 50% recommended inorganic fertilizer. Our results showed that rattlepod and paddy straw composts gave similar results in tomato growth and yield, and they were better than other plant composts tested. The application of 50% inorganic fertilizers combined with plant compost had the higher yield as compared to recommended inorganic fertilizer treatment. This implied that the use of plant compost could reduce the use of inorganic fertilizers while maintaining higher yield than using inorganic fertilizers only. The soil chemical properties was improved after application of plant compost. Keywords: inorganic fertilizer, plant compost, tomatoes